2014
DOI: 10.1371/journal.pone.0114665
|View full text |Cite
|
Sign up to set email alerts
|

Protective Association of Tumor Necrosis Factor Superfamily 15 (TNFSF15) Polymorphic Haplotype with Ulcerative Colitis and Crohn's Disease in an Indian Population

Abstract: BackgroundTumor necrosis factor superfamily (TNFSF) proteins are involved in the genesis of inflammatory bowel disease (IBD). We examined the association of seven single nucleotide polymorphisms (SNP) in the TNFSF15 gene with Crohn's disease (CD) and ulcerative colitis (UC) in the Indian population.MethodsSeven SNPs in the TNFSF15 gene (rs10114470, rs3810936, rs6478108, rs4263839, rs6478109, rs7848647 and rs7869487) were genotyped in 309 CD patients, 330 UC patients and 437 healthy controls using the Sequenom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…However, only 5 SNPs, namely rs2395185 (HLA-DRA), rs3024505 (IL10), rs6426833 (RNF186), rs3763313 (BTNL2), and rs2066843 (NOD2), retained significance after Bonferroni correction. Another Indian study reported a strong protective association with TNFSF15 (tumour necrosis factor superfamily) gene polymorphisms and IBD in the Indian population [39] . TNFSF15 has also been associated with an IBD risk in studies from Japan and the UK [40,41] .…”
Section: Geneticsmentioning
confidence: 98%
“…However, only 5 SNPs, namely rs2395185 (HLA-DRA), rs3024505 (IL10), rs6426833 (RNF186), rs3763313 (BTNL2), and rs2066843 (NOD2), retained significance after Bonferroni correction. Another Indian study reported a strong protective association with TNFSF15 (tumour necrosis factor superfamily) gene polymorphisms and IBD in the Indian population [39] . TNFSF15 has also been associated with an IBD risk in studies from Japan and the UK [40,41] .…”
Section: Geneticsmentioning
confidence: 98%
“…Moreover, many TL1A loci are associated with IBD susceptibility across all ethnic and age groups [11, 15, 16]. rs10114470 is a novel TL1A locus that was found to provide significant protection against both CD and UC in an Indian population [17]. However, the relationship between rs1250569, rs1042522, and rs10114470 variants and IBD susceptibility has not yet been investigated in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…We found 2,054 Cen-tiSNPs with ASB (p-value<0.05) and 1,769 CentiSNPs with ASE (p-value<0.05) associated to a complex trait in the GWAS catalog (Table S5,S6) or with a PPA>0.1 from fgwas [12]. We were able to dissect the molecular mechanism for rs3810936, a variant associated with risk for Crohn s disease in multiple populations [40,41,42,43] (Figure 3e,f). This variant is a CentiSNP for the factor Hmx3 (Nkx5-1) and we find ASB for NFKB (p-value=0.006) in the BiT-BUNDLE-seq assay and ASE (p-value=0.034) in both directions in the BiT-STARR-seq.…”
Section: Figure 2: Ase For Individual Transcription Factors A) Qqplomentioning
confidence: 88%
“…BiT-STARR-seq z score is the z score from meta-analysis of ASE for nine experimental replicates. GWAS OR is the odds ratio from rs3810936 alternate allele with Crohns disease [40,41,42,43]. All scores are signed relative to the risk allele, which is the alternate allele.…”
Section: Figure 2: Ase For Individual Transcription Factors A) Qqplomentioning
confidence: 99%